Розпізнавання друкованого тексту з картинки і конвертація його в друкований формат - Сіденко, Д. А. (ХНУРЕ, 2021)
Typing a lot of text can take a long time, even if it's just automatic reprinting of information, for example, from a picture, when there is a photo of printed text material. Therefore, quite often there is a need to automate this process. This article will discuss how to automatically recognize printed text from a picture and convert it to print format.
Keywords: друкарська форма